Peran Petugas KIA Terhadap Deteksi Dini BBLR Pada Ibu Hamil Di Puskesmas Poasia Tahun 2023 - Adel, Rei Restu Adelia; Bahar, Hartati; Kamrin Kamrin (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Indonesia ranks ninth in the world with more than 15.5% of newborns experiencing LBW annually. The purpose of this study is to explain the role of MCH officers in early detection of LBW in pregnantwomen at the Poasia Health Center. This type of research is a qualitative study with a phenomenological approach. The informant determination technique was carried out by purposive sampling. Data collection used interviews and observations with research informants, namely 2 MCH officers and 2 pregnant women who had their pregnancies checked at the Poasia Health Center. pregnant at risk of LBW or not. As well as meeting ANC standards, however, the knowledge possessed by pregnant women who check their pregnancies at the Poasia Health Center is still lacking because pregnant women do not receive counseling related to LBW from KIA officers.